Belasting, Local Elites, and Indigenous Resistance in Gorontalo, Indonesia, 1856-1942 - Joni Apriyanto; Yety Rochwulaningsih; Singgih Tri Sulistiyono; Haryono Rinardi (Journal Of Social Science (JoSS), 2026)
This study examines the implementation of the Dutch colonial taxation system (belasting) in Gorontalo, Indonesia, from 1856 to 1942 and its socio-economic and political consequences for indigenous communities. Colonial taxation functioned not only as a fiscal mechanism but also as an instrument of political domination that reshaped agrarian relations, social hierarchies, and local governance. The study aims to analyze the structure of colonial taxation, the role of local elites in tax administration, and the forms of indigenous resistance that emerged in response to colonial fiscal policies. Using a historical research method, the study applies four stages of historical inquiry: heuristics, source criticism, interpretation, and historiography. Primary data were collected from colonial archives, including Koloniaal Verslag, Memorie van Overgave, and Politiek Verslag, supported by secondary literature on colonial governance and resistance movements. The findings reveal that the belasting system intensified economic dependency through land taxes, poll taxes, maritime levies, and corvée labor obligations. Indigenous elites played ambivalent roles, serving both as colonial collaborators and as occasional supporters of local resistance. Colonial taxation accelerated land dispossession, social stratification, and market dependency among indigenous communities. Resistance emerged in both passive and overt forms, including tax evasion, migration, protests, and attacks on colonial administrative facilities. The study concludes that belasting in Gorontalo served as a central mechanism of colonial control while simultaneously provoking indigenous resilience and resistance, contributing significantly to the historiography of colonialism in the non-Javanese peripheries of the Dutch East Indies.